A scalable method for preparing Cu electrocatalysts that convert CO2 into C2+ products - Kim, Taehee; Palmore, G. Tayhas R. (Nature Publishing Group, 2020)
Development of efficient catalysts for selective electroreduction of CO2 to high-value products is essential for the deployment of carbon utilization technologies. Here we present a scalable method for preparing Cu electrocatalysts that favor CO2 conversion to C2+ products with faradaic efficiencies up to 72%. Grazing-incidence X-ray diffraction data confirms that anodic halogenation of electropolished Cu foils in aqueous solutions of KCl, KBr, or KI creates surfaces of CuCl, CuBr, or CuI, respectively. Scanning electron microscopy and energy dispersive X-ray spectroscopy studies show that significant changes to the morphology of Cu occur during anodic halogenation and subsequent oxide-formation and reduction, resulting in catalysts with a high density of defect sites but relatively low roughness. This work shows that efficient conversion of CO2 to C2+ products requires a Cu catalyst with a high density of defect sites that promote adsorption of carbon intermediates and C-C coupling reactions while minimizing roughness.